Safeguarding the National Airspace of Indonesia under the Framework of International Air Law - Harry Purwanto (Jurnal Hukum Novelty, 2021)
Introduction to the Problem: The vast territory of Indonesia requires careful thought in realizing an effective defense system to maintain its territorial integrity and the safety of the nation. To ensure the effectiveness of the country's broad defense system requires great strength, high mobility, and early detection capability. The development of Indonesia's defense force should not merely be oriented towards the land territory, but it must also be optimized towards the country’s sea and air forces.Purpose/Objective Study: This study examines the airspace protection system implemented by Indonesia to protect the security of the country from threats.Methodology: The research design is exploratory as this paper aspires to explore the basis of air defense identification zone.Findings: The Indonesian Government has taken legal measures by regulating restricted airspace, air defense identification zones, as well as identifying types of violations committed by foreign aircraft. Both national and international laws allow Indonesia to establish air defense identification zones.Paper Type: General Review